2002
DOI: 10.1097/00002030-200211080-00007
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of replication-competent HIV in both memory and naive CD4 T cell subsets in patients on prolonged and effective HAART

Abstract: In patients on prolonged and effective HAART, the pool of infected CD4 T lymphocytes consists predominantly of memory cells but also contains naive cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…The T CM nature of pTfh cells could allow them to persist within total memory pool and contribute to HIV latency (10,55). The inducible HIVp24 assay is simple to perform, with high degree of precision which could screen for HIV reservoirs and complement existing reservoir assays for HIV.…”
Section: Discussionmentioning
confidence: 99%
“…The T CM nature of pTfh cells could allow them to persist within total memory pool and contribute to HIV latency (10,55). The inducible HIVp24 assay is simple to perform, with high degree of precision which could screen for HIV reservoirs and complement existing reservoir assays for HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, HIV-1 Nef protein induces Thelper-cell depletion in an in vivo transgenic mouse model (14-17, 21, 24, 25, 33, 59), although it is not clear whether (i) this effect is due to intracellular or extracellular Nef protein or (ii) this effect is a developmental consequence of constitutive expression of the transgene or a model for Nef effect in HIV infection. Further, in patients receiving highly active combination antiretroviral therapy and with undetectable plasma viral RNA levels, several studies have shown (i) a stable pool of T cells harboring latent replication-competent virus (39) and (ii) detectable levels of early viral spliced mRNA in the PBMCs (67). One can speculate that, in light of the accumulated evidence concerning extracellular Nef, even in this scenario, expression of low levels of Nef could cause continued, albeit slower, depletion of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that quantification of viral DNA alone is not necessarily predictive of the size of the inducible latent reservoir and suggests caution in labeling a cellular reservoir of latent HIV-1 as "major" based solely on the frequency of infection. In addition to the memory CD4 ϩ T cell subsets, HIV-1 DNA is almost always detected in T N cells in both viremic and suppressed individuals, although with a much lower frequency than in the T CM and T TM compartments (6,7,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Interestingly, in 2013 Saez-Cirion et al reported that in some HIV-1-infected individuals who received ART within 10 weeks of primary infection, viremia could be controlled for at least 24 months posttreatment interruption (8).…”
Section: A Latent Hiv-1 Reservoir Is Established In Resting Cd4mentioning
confidence: 99%